IDENTIFIKASI FAKTOR YANG MEMENGARUHI GINI RATIO DI INDONESIA - RINI, GUSTI AYU MADE CANDRA; SUCIPTAWATI, NI LUH PUTU; UTARI, IDA AYU PUTU ARI (E-Jurnal Matematika, 2022)
Inequality in income distribution is one of the problems that are often experienced by some countries in the world. Income inequality in Indonesia is measured by an indicator named Gini Ratio. BPS Indonesia noted that in March 2021, the Gini Ratio in Indonesia was 0,384. This figure shows that Indonesia belongs to the category of moderate income inequality, which means that income in Indonesia is not well distributed or there is an inequality in income distribution. For this reason, the inequality that occurs needs to be decreased by recognizing the factors that affect it. The purpose of this study was to determine the factors that significantly affect the Indonesia’s Gini Ratio in 2016-2020 by applying panel data regression. The results show that the model chosen to represent the Indonesia’s Gini Ratio in 2016-2020 is a fixed time effect model with of 40,282%, which is significantly be affected by the human development index, population, open unemployment rate, percentage of poor people, and average hourly wage for worker.